Productivity as a determinant of labour wage in New Zealand’s construction sector - Ozturk, Mustafa; Durdyev, Serdar; Aras, Osman Nuri; Banaitis, Audrius (Technological and Economic Development of Economy, 2019)
The empirical relationships between labour wages, unemployment rate and the labour productivity index in New Zealand’s construction sector (for the period of 1983–2017) were investigated. The Johansen cointegration test and vector error correction mechanism were used to determine the existence of long-run relationships between the variables and the adjustment process of the short-run disequilibrium into the long-run equilibrium. The results show that the labour productivity index positively affects the labour wage, while the effect of unemployment rate is negative in the long run. That is, the more productive the labour, the more the wages earned. Related statistical tests on the residuals proved that the model and its findings are reliable.First published online 20 June 2019